Critically ill infant with multisystem inflammatory syndrome related to COVID-19 - Arturo A. Canul-Euan; Gabriela Solís-Jiménez (Permanyer, 2021)
Background: COVID-19 has become a threat to global public health. However, severe forms of COVID-19 presentation in children are rare. We present the case of an infant with COVID 19-related multisystem inflammatory syndrome. Case report: We describe the case of an 8-month-old infant who had contact with COVID-19 positive adults. The infant began with mild symptoms of the disease but rapidly progressed to a critical form of presentation: initially with epileptic status, and upon admission with laboratory evidence of inflammation, severe systemic condition with multiple organ failure, and a positive nasopharyngeal SARS-CoV-2 PCR test. The infant died 7 days after admission. Conclusions: The spectrum of COVID-19 presentation in children under one year of age is variable, and there are still no established criteria for diagnosis and treatment. All infants presenting a severe disease with multiple organ involvement at admission in times of pandemic require a thorough medical history to consider SARS-CoV-2 infection until proven otherwise.